The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.oraloncology.2020.104937
|View full text |Cite
|
Sign up to set email alerts
|

The 8th TNM classification for oral squamous cell carcinoma: What is gained, what is lost, and what is missing

Abstract: The 8th TNM edition remarkably changed the classification of T and N categories for oral squamous cell carcinoma (OSCC). The present study aims at evaluating the improvement in prognostic power compared to the 7th edition, pros and cons of the modifications, and parameters deserving consideration for further implementations. Materials and methods: All OSCCs treated with upfront surgery at our institution between 2002 and 2017 were included. Demographics, clinical-pathological and treatment variables were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…However, only patients with a high metastatic nodal count, namely those included in the N3a and N3b categories, showed a significantly worse prognosis. This is in line with other reports which demonstrated that the negative prognostic impact of a high number of positive nodes can also outweigh the detrimental effect of ENE [ 19 ]. While the TNM pN lacked in prognostic stratification, the pN-N+ classification succeeded in creating a clear distinction at least between patients with low- and high-nodal disease burden, namely between N2 and N3a categories, while the difference between N1 and N2, and between N3a and N3b, was not significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, only patients with a high metastatic nodal count, namely those included in the N3a and N3b categories, showed a significantly worse prognosis. This is in line with other reports which demonstrated that the negative prognostic impact of a high number of positive nodes can also outweigh the detrimental effect of ENE [ 19 ]. While the TNM pN lacked in prognostic stratification, the pN-N+ classification succeeded in creating a clear distinction at least between patients with low- and high-nodal disease burden, namely between N2 and N3a categories, while the difference between N1 and N2, and between N3a and N3b, was not significant.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous classifications, the major emphasis was put on lymph nodes laterality and size, while nodes numerosity was still overlooked. However, increasing evidence shows that the absolute count of metastatic lymph nodes strongly predicts cancer mortality [17][18][19]. Therefore, an alternative nodal classification (called pN-N+ classification), based on lymph nodes numerosity and ENE, was developed and tested, demonstrating good prognostication capability [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with the former 7th TNM (7TNM) version, points to the existence of a number of differences with a valuable impact on the choice of treatment. This interesting study consolidates the conclusions of others [ 5 , 6 ], by suggesting that 8TNM provides a better estimation of the risk of T3 OSCC, a T category virtually non-existent in the 7TNM. The authors, following a previous paper from Mirian et al [ 7 ], suggest how tumor staging could be improved by closer monitoring of the number of metastatic lymph nodes, among other parameters.…”
supporting
confidence: 88%
“…Explicit portrayal is the key for the choice of a right technique for treatment, the conceivable result and restriction for certain activities. [16][17]…”
Section: Tnm Stage Classificationmentioning
confidence: 99%